ANALISIS KESETARAAN GENDER DALAM PERTUMBUHAN PENDAPATAN PERKAPITA DI SUMATERA UTARA - Elvina Harahap (Universitas Negeri Medan, 2013)
One of the indicators are taken into account in measuring the success of development is the construction of a gender perspective. Development efforts that have been aimed at improving the welfare of the community, women and men, was not able to provide equal benefits between women and men. This study aims to determine the effect of gender equality in education, health and employment to the growth of income per capita in the province of North Sumatra in the period 2004-2009 (Pool Data) Fixed Effect estimation method. The results suggest that promoting gender equality in education, health and employment have a positive influence on per capita income. Restrict women's access to educational resources, health and employment, it can hamper local economic development. Therefore, fikir patterns, behavior, culture, and policies that lead to discrimination between women and men need to be changed and removed. More than just economic, gender equality is a form of respect for human rights as well as empower people, men and women, to gain access, participation, control and benefit equally in development..